AI SYSTEMS FOR OPTIMIZING ENERGY PROCESSES: INNOVATIVE APPROACH TO THE SUSTAINABLE DEVELOPMENT OF ENTERPRISE - DEGTIAREVA, Olga; КUKLINOVA, Tетіана; КUKLINOVA, Sofiia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The paper presents the results of a study dedicated to modern digitization processes in the energy sector, in particular implementation of Artificial Intelligence (AI) systems for optimizing energy processes. The study deals with the key aspects of the AI system’s implementation in energy processes. A special focus was given to the terminology in the context of the system approach to the AI-related categories.The article provides results of the corresponding research with the following objectives: to argue the concept of the AI-systems in the energy sector; consider the main stages of the AI-system implementation for optimizing processes within the enterprise's energy complex, analyze the know-how regarding AI-system usage in the energy sector of Ukraine: determine AI challenges and perspectives; recommend the controlling system to mitigate AI-risks. We concluded that the energy companies are able to optimize energy processes by implementation of the AI systems.The study revealed the main features of AI systems, their implementation within energy companies for optimizing business processes, features of the controlling system to manage AI-related risks, and ways to develop AI systems within companies and energy processes. As far as implementation of the AI systems is usually followed by socio-economic consequences we paid attention to the following AI-related aspects as well: 1) the impact of AI systems on technological unemployment; 2) consideration of organizational changes depending on the level of the AI systems use within energy companies; 3) recommendations for support of AI systems in energy processes in the post-war period in the Ukrainian economy. Thus, the research underscores the pivotal role of AI systems in fostering a more resilient and environmentally conscious approach to energy management, thereby contributing to the long-term sustainable development goals of enterprises.
Keywords: Аtificial Іntelligence systems; sustainable development; digitalization; Artificial Intelligence; management; energy management; energy processes; AI